ACTION TIME: freud's "the moses of michelangelo". Issue 5 (2nd September 2020) - Stables, Wayne
Abstract: Our actions, even the quietest, are liable to become occasions for inculpation. But what kind of action would remain immune to the act of judgement? Such an action is made manifest in Michelangelo's Moses . Freud's cinematic reading of the sculpture yields a concern with what Moses does not do. Neither the origin nor the outcome of an action proves decisive but rather "the remains of a movement that has already taken place." Such a remainder troubles the ascription of agency to action by undermining the fantasy of homogenous time which underlies it. Continuity is revealed as the semblance of an imperceptible series of temporal omissions. The paper aims not only to bring to light the radical potential harboured in Freud's approach to the Moses but to account for the reason he arrests its appearance.